INCENTIVOS FISCAIS (SUDAM E SUFRAMA) E A DINÂMICA INDUSTRIAL E AGROPECUARIA NA REGIÃO NORTE - Nascimento, Luiz Roberto C. (2009)
The viability of fiscal incentives programmes have been examined through many methodological approaches and in many different studies. Despite that, this subject still demands attention. Thus, having the Brazilian North Region as a case study, this paper analyses two fiscal incentives schemes there adopted (FINAM and SUFRAMA) and their impacts on the region's economic dynamic through the period 1970-96. The paper adopts the so-called shift-share methodology to access these impacts and concludes that the incentives do production from SUFRAMA seems to lead to better results in relation to those obtained by FINAM.